Prognostic Factors of Paraquat Toxicity in Urmia: Seven-Year Retrospective Investigation: Prognostic factors of paraquat toxicity - Majidi, Mohammad; Delirrad, Mohammad; Mostafazadeh, Ayda (International Journal of Medical Toxicology and Forensic Medicine, 2025)
Background: Paraquat is a very fatal herbicide. It causes such serious complications as acute respiratory distress syndrome, fibrotic lungs, metabolic acidosis, cardiac shock, renal failure, and even death. For this reason, in this study, the prognostic factors of paraquat intoxication were evaluated. Methods: In this retrospective study, all paraquat-intoxicated patients hospitalized to Taleghani Hospital in Urmia, Iran, from 2014 to 2020 were assessed. The demographics, clinical, and laboratory findings were evaluated using a checklist and investigated in relation to the patients’ outcomes. Then, the collected data were analyzed using SPSS version 21. Results: Our study evaluated 102 cases (71 males & 31 females). The mortality rate was 46.1% (31.4% in males and 14.7% in females) in these patients. The patients’ age was (31.4 years ± 13.3 standard deviation) (min=14, max=79). The Median ingestion amount of paraquat was 174 ml (min = 10 ml, max = 1500 ml). Nausea 86 (84.3%), vomiting 78 (76.5%), mucosal lesions of the oral cavity and pharynx 60 (58.8%), epigastric pain 35 (34.3%), and acute respiratory failure 30 (29.4%), loss of consciousness 13 (12.7%), were the important findings in the investigated patients, respectively. Significant relationships (P<0.05) were observed between the patients’ outcomes and demographic (the ward & duration of admission), clinical findings (the level of consciousness, vomiting, epigastric pain, acute respiratory failure, hypertension, & sinus bradycardia) and laboratory indices, such as White Blood Cells, Bilirubin, Serum Hco3, Aspartate transaminase (SGOT), Alanine aminotransferase (SGPT), Creatinine, Blood glucose, Platelet, Calcium, Potassium, Leukocytosis, Metabolic acidosis, Hypokalemia. Conclusion: Some factors, especially laboratory and clinical features, can be applied as a guide to the severity of patients’ poisoning, which can be used for effective management by healthcare providers. However, more studies will be needed to clarify absolute prognostic factors in patients with paraquat toxicity.